2013
DOI: 10.1116/1.4821635
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature plasmas in carbon nanostructure synthesis

Abstract: Plasma-based techniques offer many unique possibilities for the synthesis of various nanostructures both on the surface and in the plasma bulk. In contrast to the conventional chemical vapor deposition and some other techniques, plasma-based processes ensure high level of controllability, good quality of the produced nanomaterials, and reduced environmental risk. In this work, the authors briefly review the unique features of the plasma-enhanced chemical vapor deposition approaches, namely, the techniques base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 132 publications
0
56
0
Order By: Relevance
“…Plasmas can ensure simultaneously high temperatures, highly reactive environment-electrons, ions, free radicals, energetic photons (UV radiation). For example, it has been shown that in plasma-enhanced chemical vapor deposition [1,3,5,7,9,10] a high level of control over material fluxes, heating and concomitantly the structure and properties of formulated materials can be achieved. This method makes use of a substrate inserted in a low-pressure plasma environment.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Plasmas can ensure simultaneously high temperatures, highly reactive environment-electrons, ions, free radicals, energetic photons (UV radiation). For example, it has been shown that in plasma-enhanced chemical vapor deposition [1,3,5,7,9,10] a high level of control over material fluxes, heating and concomitantly the structure and properties of formulated materials can be achieved. This method makes use of a substrate inserted in a low-pressure plasma environment.…”
Section: Introductionmentioning
confidence: 99%
“…Such self-standing graphene sheets are alternative to horizontal graphenes supported by solid surfaces because they have an obvious advantage related to the fact that both surfaces and at least three open edges can be utilized in applications while surface-bound counterparts effectively use one surface. In this respect, a new approach for a large-scale fabrication of graphene flakes in magnetically enhanced dc arc discharge is presented by Levchenko et al [10]. The graphene flakes are produced using a carbon anode, which is a rod with a hole in the center.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations